Implementation Of Patient Safety Program In The Surgical Room By Nurses Based On The Rules Of The Royal Prima Medan Hospital In 2021 - Dhea Sandhes Barus; Maya Sari Mutia; Ulina Karo-karo (International Journal of Health and Pharmaceutical (IJHP), 2022)
Currently, the issue of patient safety is getting serious attention from the government. Hospitals must fulfill the patient's right to security and safety while in hospital treatment. Patient safety is a serious global public health problem. Medical errors can be caused by both system and human factors. This research was conducted at the Royal Prima Hospital Medan with the issue of patient safety at the Central Surgical Installation (CSI). The formulation of the problem in this study is about the implementation of patient safety programs by nurses in the operating room based on the rules of the Royal Prima Hospital Medan in 2021. The type of research used is descriptive using a phenomenological approach which is a type of qualitative research. The population in this study were all nurses who worked in the Central Surgical Installation ward (CSI) of the Royal Prima Hospital Medan. The total sampling was 23 nurses with inclusion criteria, willing to be respondents and not on vacation/leave the service facilities at the hospital. The results showed that the implementation of the patient safety program in the operating room by nurses based on the rules of the Royal Prima Hospital Medan had been implemented and had a program prepared policies and patient safety guidelines as a reference in improving the quality of health services.